Geological And Rainfall Condition As Landslide Causative Factors In Shoutern Part Of Central Java In Juni 2016 - Rokhmat Hidayat; Samuel Jonson Sutanto; Moh. Deddy Munir (Pusat Litbang Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2016)
On June 19, 2016, landslides occurred in some areas located in the South Central Java (Purworejo, Kebumen, and Banjarnegara). One day before the incident, there was a high intensity of rainfall in the surrounding areas. A study of the geological conditions as well as the characteristics of rainfall triggering those landslides has been carried out. Field investigations, geological analysis, and dailly to hourly rainfall analises have been conducted. Moreover, some necessary mitigation measures are discussed. The results of this study show that the main type of landslides is consisted of loosened components included in translational slides. The contact zone between weathered bedrocks and materials above causes the landslides. A porous soil in the top layer with fresh rock underneath may potentially be a sliding plane of this landslide. The different in soil thickness produces different landslide volume. Rainfall intensity during the landslide was 100-323 mm/day with intensity of 16-22 mm/hour for about 5 hours. Landslides occurred on the steep areas with slopes between 25-35. Generally, there are several measures that can be applied at the landslide sites, such as relocation of communities affected by landslides, and simple Early Warning System installed with rainfall sensor-based equipment